2018
DOI: 10.3832/ifor2318-011
|View full text |Cite
|
Sign up to set email alerts
|

Climate effects on growth differ according to height and diameter along the stem in Pinus pinaster Ait.

Abstract: Climate-growth relationships in forest trees are increasingly the focus of research aimed at understanding and assessing responses to climate change. Many studies have been confined to annual radial growth at breast height as an easy-to-measure dendrological standard variable, although its validity as a proxy for overall annual growth patterns in trees has scarcely been addressed. In this study, we test this hypothesis by exploring additional information on climate-growth relationships as well as analyzing bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
6
0
3
Order By: Relevance
“…This indicated that the carry-over effects of the 2018 drought stress might have negatively influenced the recovery of the trees in 2019. One possible explanation for this might be that the height and radial increment in most conifers is mainly predetermined during the year previous to the growth [44]. There was also an obvious structural reason; with the cessation of growth and bud set, the newly formed bud starts to form needle primordia for the next growing season whereafter it enters an endodormant state [45].…”
Section: Genetic Variance Components and Heritability Estimatesmentioning
confidence: 99%
“…This indicated that the carry-over effects of the 2018 drought stress might have negatively influenced the recovery of the trees in 2019. One possible explanation for this might be that the height and radial increment in most conifers is mainly predetermined during the year previous to the growth [44]. There was also an obvious structural reason; with the cessation of growth and bud set, the newly formed bud starts to form needle primordia for the next growing season whereafter it enters an endodormant state [45].…”
Section: Genetic Variance Components and Heritability Estimatesmentioning
confidence: 99%
“…where BAI i is the BAI value of the i year. These indices were calculated with 4-year pre-(i-4), and post-disturbance (i+4) periods, based on previous studies (Rubio-Cuadrado et al, 2018b, 2018a, using the pointRes package in R (van der Maaten-Theunissen et al, 2015). The differences between sites were analyzed through Mann-Whitney U tests.…”
Section: Climate-and Drought-growth Relationshipsmentioning
confidence: 99%
“…El crecimiento difiere en las dos estaciones estudiadas (primavera y otoño), siendo mayor en primavera que en otoño (que incluye también el parón veraniego), aunque la meteorología solo afecta al crecimiento primario primaveral. Estudios previos han señalado que P. pinaster se comporta como una especie policíclica (Rubio-Cuadrado et al, 2018;Vieira et al, 2019;Aldea et al, 2021), por lo que nuestros resultados confirman este hecho. La mayor duración de las sequías estivales que se prevé con el cambio climático en la cuenca del Mediterráneo tendrá como consecuencia la reducción de la ventana de crecimiento primaveral, lo que afectará al desarrollo del regenerado (Chambel et al, 2007;Ruano et al, 2009, entre otros).…”
Section: Discussionunclassified
“…En cuanto al crecimiento del regenerado de esta especie, las coníferas mediterráneas, como es el pino resinero, suelen presentar un patrón bimodal de actividad en el cambium y los tejidos meristemáticos, que se encuentra frecuentemente modulado por las condiciones climáticas y les lleva a generar dos ciclos anuales de crecimiento diametral y en altura (Jordy, 2004;Rubio-Cuadrado et al, 2018;Aldea et al, 2021). Además del control climático del crecimiento (Ruano et al, 2009), se han encontrado influencias de la competencia inter e intra-específica (Calama et al, 2017), de características intrínsecas de la planta, como su propio tamaño o el estado ontogénico (de la Mata et al, 2014) y del tratamiento selvícola escogido (Rodríguez- García et al, 2010).…”
Section: La Gestión Forestal De Pinus Pinaster En Un Contexto De Camb...unclassified
See 1 more Smart Citation